Pengaruh Kompetensi, Komunikasi Interpersonal dan Sikap Petugas terhadap Kepuasan Ibu Hamil Pelayanan USG Baloi Permai Batam - Citra Dessy; Sabri Sabri; Hengky Oktarizal (Asosiasi Ide Bahasa Kepri, 2026)
This study aims to analyze and determine the influence of work competence, interpersonal communication, and staff attitudes on the satisfaction of pregnant women receiving ultrasound (USG) services at Baloi Permai Public Health Center, Batam City. Specifically, this study seeks to examine the extent to which staff work competence—comprising knowledge, understanding, and skills—contributes to patient satisfaction. In addition, the study aims to assess the effect of interpersonal communication, characterized by openness, clarity of information, and supportive interaction, in establishing effective relationships between healthcare providers and patients. Furthermore, this research evaluates the influence of staff attitudes, reflected in friendliness, empathy, respect, and patience, on the perceived satisfaction of pregnant women. Beyond partial effects, this study also aims to investigate the simultaneous influence of these three variables on patient satisfaction. Therefore, the findings are expected to provide a comprehensive understanding of the key factors affecting the satisfaction of pregnant women in ultrasound services, as part of efforts to improve the quality of healthcare services at primary healthcare facilities.